2019
DOI: 10.1021/acs.inorgchem.8b03514
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphine Sterics in Strained Aminophosphine Chelate Formation

Abstract: The preparation of four-membered aminophosphine (PN) chelates from common metal precursors has largely evaded realization because of the ring strain associated with these species. We report a straightforward approach to the synthesis of such PN metallacycles using simple α-PN ligands analogous to the popular class of small-bite-angle diphosphinomethane ligands. It is demonstrated that bulky phosphine substituents are important to the formation of these chelates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…56 Additionally, work from both Grotjahn and Love has shown that larger phosphine substituents favor the formation of "strained" 4-membered PNchelates. 57,58 The bulky R-groups on phosphine are proposed to lower the ring strain through the Thorpe-Ingold effect compensating for the steric repulsion offered by the same Rgroups. Thus, overall, the sterics of the t Bu groups and the Thorpe-Ingold effect both favor the ionic [ LH Ir][X] species over the neutral [ LH Ir-X] species in these Ir-complexes.…”
Section: Discussion Of the Mlpt Equilibria For The Chloride Bromide A...mentioning
confidence: 99%
“…56 Additionally, work from both Grotjahn and Love has shown that larger phosphine substituents favor the formation of "strained" 4-membered PNchelates. 57,58 The bulky R-groups on phosphine are proposed to lower the ring strain through the Thorpe-Ingold effect compensating for the steric repulsion offered by the same Rgroups. Thus, overall, the sterics of the t Bu groups and the Thorpe-Ingold effect both favor the ionic [ LH Ir][X] species over the neutral [ LH Ir-X] species in these Ir-complexes.…”
Section: Discussion Of the Mlpt Equilibria For The Chloride Bromide A...mentioning
confidence: 99%
“…3 , completely consumed within one hour under in situ NMR conditions, see also ESI, † S3 and Table S6) and the formation of Ph 3 P, [Ph 4 P]Cl and another intermediate (Int1). The structure of Int1 could be assigned based on a combination of its 31 P chemical shift, 1 H– 31 P HMQC experiments and comparison with literature data, 28 which suggest a TDAE skeleton that is coordinated to a Ph 2 P moiety via a methylene group ( Fig. 3 and see also ESI, † S6 and Fig.…”
mentioning
confidence: 91%
“…The situation is different with the methylene-bridged diphosphine dppm, despite the fact that both ddpe and dppm were reported at the same time . Dppm and derivatives have also been widely used in coordination chemistry, and many complexes acting as bidentate species are known . In spite of this, the four-membered rings they form are quite strained and for this reason, unlike dppe, dppm shows a strong tendency to act as a bridging ligand between two metal centers, which are in close proximity .…”
Section: Introductionmentioning
confidence: 99%